Strengthening The Poor Fishermen Families Life in Setapuk Besar Village Through Coastal Independent Community Empowerment Program - Mukhlis, Mukhlis (Technium Social Sciences Journal, 2021)
This research study focuses on implementing the Independent Coastal Community Empowerment Program in the Life of Poor Fishermen's Families in Setapuk Besar Village, Singkawang Utara District Singkawang City. This paper aims to explain the poverty characteristics of fishing families in Setapuk Besar village and find a model for improving families' economic life in coastal communities in Setapuk Besar Village. This research is a type of case study research. The method used in this research is qualitative methods and data collection techniques through in-depth interviews, observation, and documentation study. This research found out that the purpose of the institution was formed to increase public knowledge with that hope. Public awareness can be the principal capital in realizing people's lives in coastal areas empowered in the economic, social, and educational fields.